Clinicoepidemiological and laboratory findings of COVID positive patients presenting to a tertiary care centre in South India: A retrospective analysis - Diya Biju; Soumya Johnson; Chithra Valsan; A.B Prasad; Praveenlal Kuttichira (Elsevier, 2022)
Background: SARS CoV2 continues to pose a threat to human race even after one year of its outset in China. Observational studies from across the world have shown huge disparity in the clinicoepidemiological and laboratory features of this disease. In this study we attempt to assess the clinical, epidemiological and laboratory parameters of COVID 19 positive patients in this geographic location. Methods: This is a descriptive retrospective study of patients who were tested positive for SARS-CoV-2 at a tertiary care centre in central Kerala, India between July 16, 2020 and November 30, 2020. The clinicoepidemiological and laboratory parameters of the confirmed patients were collected from the laboratory and hospital records and analysed. Results: A total of 1051 patients were tested positive during the study period. The mean age of the patients was 45.7 years ± Standard Deviation (SD): 8.68; 51.76% were male. Among them 658 (62.61%) were symptomatic and 393(37.39%) were asymptomatic; males (54.7%) were more symptomatic than females (45.3%). The common presenting symptoms were fever (43.58%), cough (21.50%), myalgia or fatigue (10.28%). Lymphocytopenia was more in males than females. Laboratory parameters such as Serum Ferritin, Alanine Transferase, Aspartate Transferase, Sodium level were elevated in males compared to female. Conclusion: The common symptoms in our study could emphasize on identifying potential patients in this geographic area. Asymptomatic patients should be monitored and investigated for effective control of the disease. A knowledge about the disease presentation in each geographic area is important in planning the effective management strategies since the features are varied from place to place.